In-Hospital Mortality following Proximal Femur Fractures in Elderly Population - Ram, Ganesan G.; Govardhan, Praveen (The Surgery Journal, 2019)
Context In India, hip fracture crude incidence above the age of 50 years was 129 per 100,000.Aims The aim of this study is to analyze the in-hospital mortality following proximal femur fractures in elderly Indian population.Methods and Material The study was done in Sri Ramachandra Medical Center, Chennai, India. Patient's records were retrospectively evaluated for a period of 3 years from January 1, 2015 to January 1, 2018. The inclusion criteria were patients both male and female aged more than 65 years admitted with the diagnosis of neck of femur or intertrochanteric or subtrochanteric fractures. The exclusion criteria were patients having any associated fracture or previous hip fracture history or diagnosed primary or secondary malignancies. To evaluate any surgical delay two groups were formed. After eliminating cases based on exclusion criteria, we had 270 patients for evaluation.Statistical Analysis Used The collected data were analyzed with IBM.SPSS statistics software 23.0 Version. To describe about the data descriptive statistics frequency analysis, percentage analysis were used for categorical variables and the mean and standard deviation (SD) were used for continuous variables. To find the significant difference between the bivariate samples, Student's t-test and analysis of variance (ANOVA) were used. The p-value of 0.05 is considered as significant level.Results We had a total of 24 mortalities with 15 males and 9 females. The in-hospital mortality of patients who underwent replacement surgeries for proximal femur fractures was 14 in our study. Sixteen of the in-hospital mortality patients had low Parker's mobility score. Twenty patients had mortality when surgery was delayed more than 48 hours.Conclusions In-hospital mortality in elderly patients having proximal femur fracture increases significantly if the patient was having low-preoperative mobility status, if surgery was delayed more than 48 hours, and if patient undergoes replacement surgeries.
Keywords: mortality; proximal femur; Parker's mobility score; replacement surgeries; elderly